(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2016)
The philosophical notion of Hyperobject, as proposed by Timothy Morton (2013), might be a useful tool to reframe some of the key issues in human-environment relationships. This new concept could bridge the ‘once sisters’ disciplines of philosophy and geography, proposing a new way to analyze the biggest environmental phenomena of our times. In this paper, we will define what Hyperobjects exactly are, starting with their philosophical roots and the implications for the discipline of geography: the traditional notion of “World” itself is going to be challenged. The aim of this paper is obviously not to write a complete list of every Hyperobject, but to start a catalogue of them. For this reason, to support our arguments, we will discuss some of the most evident examples of Hyperobjects, such as Global Warming, landscape, abandon and waste; an array of very different phenomena that share some common traits: they are all shaping the geographies of our time, and they all have what an object need to be considered an Hyperobject.